New method for the mathematical derivation of the ventilatory anaerobic threshold: a retrospective study - Nishijima, H.; Kominami, K.; Kondo, K.; Akino, M.; Sakurai, M. (BMC Sports Science, Medicine and Rehabilitation, 2019)
Ventilatory anaerobic threshold (VAT) is a useful submaximal measure of exercise tolerance; however, it must be visually determined. We developed a new mathematical method to objectively determine VAT.